Arabic, Islam, and the Allah Lexicon: How Language Shapes Our Conception of God by John A. Morrow, ed. (USA: Edwin Melton Press, 2006. 317 pages. (American Journal of Islam and Society, 2008)
Divided into five chapters plus a bibliography and an index, Arabic,Islam, and the Allah Lexicon explores Allah-centric expressions in Arabicand their far-reaching influence on the linguistic behavior of native Arabicspeakers in particular and Muslims speaking their own languages in general.It clearly demonstrates how Islam’s advent constituted a turning point in thehistory of theArabic language by introducing numerous theocentric expressionsreflecting God’s oneness, as opposed to the practice of polytheism inthe pre-Islamic era. These expressions have successfully become the bannerof day-to-day communication in Arab communities and, to a lesser extent,in non-ArabMuslim cultures. TheAllah lexicon inArabic has indeed shapedthe concept of God inArab and/or Muslim culture; henceAllah’s omnipresence, omnipotence, and omniscience are linguistically felt in times of prosperityand adversity alike ...